Measuring Collection Diversity via Exploratory Analysis of Collection Metadata - Pedersen, Jordan (The Serials librarian, 2022)
As libraries commit to equity, diversity, and inclusion (EDI) initiatives, it is critical to measure the strengths and weaknesses of collections in response. Building off already established approaches of collection diversity audits, the author argues that it is possible to use MARC metadata to perform exploratory analyses at a large scale. This paper discusses the process of planning, preparing the data, and performing an analysis, following the trajectory of an analysis of the 2.8 million geographic subject headings present in the University of Toronto Libraries’ MARC records. The tools developed during this project are cited and available for reuse.